(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The purpose of this article is to demonstrate current trends of social media in these day, as well as, you will be give some information about the role of social media during learning and developing speaking skill. In addition, there are variety of apps and brain games in order to improve speaking skill.